Penerapan Prinsip Arsitektur Organik pada Gedung Convention Hall di Universitas Lancang Kuning - Hakim, M. Azizul; Masrul , Wati; Nurdin, Apriliana Hidayati (Universitas Medan Area, 2025)
Convention Hall can be interpreted as a building with the function of meeting activities carried out by a group of people in discussing an activity either nationally or internationally. The design of the Convention Hall building in a university environment aims to provide a multifunctional space that can support various academic, social, and cultural activities. This building is expected to be a center of activity that supports the internal needs of the campus, such as seminars, conferences, graduations, scientific discussions, and student events, as well as being open to external activities such as exhibitions and community events. In addition to fulfilling its main function as a meeting center, this building is also equipped with supporting facilities, such as a waiting room, pantry, exhibition area, and audio-visual technical room. The design research for this convention hall building uses an organic architectural approach, namely architecture that harmonizes buildings and the surrounding nature of the site using its principles.